Social modulation of the daily activity rhythm in a solitary subterranean rodent, the tuco-tuco (Ctenomys sp) - Barbara Mizumo Tomotani; Juan Pablo Amaya; Gisele Akemi Oda; Veronica Sandra Valentinuzzi (Sleep Science, 2016)
South American subterranean rodents are mainly described as solitary and mutual synchronization was never observed among individuals maintained together in laboratory. We report that a single birth event was capable of disrupting the robust nocturnal activity rhythm of singly housed tuco-tucos from north-west Argentina. “Around-the-clock activity” was displayed by 8 out of 13 animals whose cages were closer to the newborn pups. However, experimental exposure to a pup vocalization did not produce a similar effect on the rhythms of adult animals. Our results indicate an effect of social interaction in the expression of biological rhythms even in solitary animals.